The Effectiveness of Providing Student Worksheets in an Effort to Improve Science Learning Outcomes for Class V Elementary School Students - Nadrah, Nadrah (Future Science / FSH-PH Publications, 2023)
This research aims; (1) to obtain an overview of the science learning outcomes of the fifth grade students of SD Negeri Kalukuang II Makassar who were taught by giving Student Worksheets, (2) to obtain an overview of the science learning outcomes of the fifth graders of SD Negeri Kalukuang II Makassar who were taught without the provision of Student Worksheets , and (3) To examine the science learning outcomes of fifth grade students of SD Negeri Kalukuang II Makassar who were taught by giving student worksheets without giving student worksheets. Based on the results of data analysis and discussion of research results, it can be concluded that; (1) The results of data analysis show that the average score of science learning outcomes for fifth grade students of SD Negeri Kalukuang II Makassar who are taught by giving Student Worksheets is 16.1563 from an ideal score of 20 with a standard deviation of 3.44, (2) The results of the analysis The data shows that the average score of fifth grade science learning outcomes at SD Negeri Kalukuang II Makassar who are taught by giving Student Worksheets is 12.5313 from an ideal score of 20 with a standard deviation of 3.689, and (3) After analyzing the data derived from If the population is normally distributed and homogeneous, a hypothesis research is conducted where the probability (P = 0.000) is smaller than (α = 0.05) so that it is stated that there is a difference between the science learning outcomes of fifth grade students of SD Negeri Kalukuang II Makassar who are taught with giving Student Worksheets -and those who are taught without giving Student Worksheets. Thus, it can be concluded that the science learning outcomes of fifth grade students of SD Negeri Kalukuang II Makassar who are taught by giving student worksheets are better than those taught without giving student worksheets.